Identification of Penicillium expansum causing postharvest blue mold decay of apple fruit - Vico, Ivana M.; Duduk, Nataša; Vasić, Miljan; Nikolić, Milica (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2015)
Penicillium expansum (Link) Thom. is one of the most important postharvest pathogensof apple fruit worldwide. It causes blue mold, a decay that can lead to significant economic losses during storage, which can also impact fruit destined for processing due to the production of carcinogenic mycotoxin patulin. Apple fruit cvs. Idared, Golden Delicious and Braeburn with blue mold symptoms were collected from five storage facilities in Serbia and nine fungal isolates were obtained. Pathogenicity of the isolates was tested and proven by artificial inoculation of healthy apples cv. Idared. In order to identify the causal agents of decay, morphological and molecular methods were used. Colony morphology and microscopic features were observed on differential media, and isolates were tested for the production of cyclopiazonic acid. Molecular analysis included PCR amplification with species specific primers for P. expansum based on polygalacturonase gene (Pepg1), universal primers for internal transcribed spacer rDNA region and primers based on β-tubulin gene. All isolates formed compact blue green colonies with characteristic earthy odor. Conidiophores were terverticillate with smooth septate stipes and conidia were smooth, globose to subglobose, born in colums. The average size of conidia was 3.38 ± 0.49 (SD) x 3 ± 0.36 (SD) μm. Using species specific primers PEF/PER the texpected amplicons of ~404 bp were obtained in all nine tested isolates and PCR conducted with the Bt-LEVUp4/Bt-LEV-Lo1 and universal ITS1/ITS4 primer pairs generated amplicons of the expected sizes of ~800 bp and ~600 bp, respectively. MegaBlast analyses of the 2X consensus of nucleotide sequences of the isolate JP1 partial β-tubulin gene and ITS region showed 99-100% and 100% similarity with several P. expansum sequences of corresponding regions of this species deposited in GenBank. Based on morphological and molecular features, the isolates obtained from decayed apple fruit collected in several storage facilities in Serbia were identified as P. expansum.
Keywords: Penicillium expansum; Postharvest decay; Apples